Explaining the Great Moderation: it is not the shocks - Domenico Giannone; Michele Lenza; Lucrezia Reichlin (European Central Bank (ECB), 2008)
This paper shows that the explanation of the decline in the volatility of GDP growth since the mid-eighties is not the decline in the volatility of exogenous shocks but rather a change in their propagation mechanism.
Keywords: E32; E37; C32; C53; 330; Great Moderation; Information; shocks; Wirtschaftswachstum; Nationaleinkommen; Volatilität; Schock; Politische Kommunikation; VAR-Modell; USA